2022
DOI: 10.1111/jasp.12863
|View full text |Cite
|
Sign up to set email alerts
|

Extreme party animals: Effects of political identification and ideological extremity

Abstract: Many Americans’ political identity is more relevant, salient, and central than their American identity. Political parties provide party members with an identity and belief system. Political identities influence identity‐based ideologies which increase affective polarization and potential anti‐social intergroup conflict between political parties. The purpose of the current research is to determine how political party identification and ideological extremity influences affective polarization for Republicans and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…As expected, there was no main effect for any predictor on the post-election ideological extremism outcome (Table 2). Our results support a social identity perspective regarding ideological extremism: the more people identify with a group, the more they become susceptible to extreme beliefs when their group considers these beliefs as group norms (e.g., Brown & Hohman, 2022;Iyengar & Westwood, 2014;Mason, 2018). Most importantly, our study expands on the findings that extreme Democrats and Republicans generally display affective extremism rather than ideological extremism (Mason, 2018).…”
Section: Discussionsupporting
confidence: 78%
“…As expected, there was no main effect for any predictor on the post-election ideological extremism outcome (Table 2). Our results support a social identity perspective regarding ideological extremism: the more people identify with a group, the more they become susceptible to extreme beliefs when their group considers these beliefs as group norms (e.g., Brown & Hohman, 2022;Iyengar & Westwood, 2014;Mason, 2018). Most importantly, our study expands on the findings that extreme Democrats and Republicans generally display affective extremism rather than ideological extremism (Mason, 2018).…”
Section: Discussionsupporting
confidence: 78%
“…Brown, J. K., et al delved deeper into the influence of the ruling party's identity and ideology on the sentiments of the two political parties within the country and, from the study, found Constructive solutions. An empirical analysis experiment was designed, where the identity of the ruling party was significantly correlated to the emotional polarization of the two parties, but the emergence of ideology slowed down the emergence of extremism [14].…”
Section: Introductionmentioning
confidence: 99%
“…Using big data analysis technology, students' learning progress and understanding can be monitored in real-time, and problems can be found and intervened in time, etc. [9][10][11][12]. The optimization of teaching methods can be based on data analysis, and teachers can implement personalized teaching strategies for the learning characteristics and needs of different students and use the interactive function of the big data platform to increase teacher-student interaction and student-to-student discussion and improve student participation and interest [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Rong Pan. Applied Mathematics and Nonlinear Sciences, 9(1) (2024)[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] …”
mentioning
confidence: 99%